Lameness in sows and the emotional consequences in the offspring - Sarmiento, Marisol Parada (2021)
Pork is the second most consumed animal protein in the world, and there are important animal welfare concerns for the over 1 billion pigs raised for meat each year. One important animal-based indicator of good welfare in pigs is the absence of lameness, which may affect up to 15% of sows globally. Lameness is an extremely painful and stressful condition which, when not identified and treated correctly, can affect animals in several ways, including through their social behavior, nutritional condition, and overall biological functioning and mental state. During pregnancy, lameness has the potential to alter developmental outcomes of the offspring by transplacental endocrine modification or epigenetic mechanisms. This study initially explored an existing dataset on lameness in sows during pregnancy in which we assessed behavioral and physiological consequences of lameness in sows and their offspring thorough measures of salivary and placental glucocorticoid concentrations in sows, and indicators of agonistic and exploratory behavior in their weaned offspring when mixed and s bjected to open field and novel object tests. Follow up studies involved systematic periodical locomotion assessments in pregnant sows on two commercial pig farms, one in Brazil (Farm 1) and one in Italy (Farm 2). A validated 0 to 5 score system was used, with 0 corresponding to easy locomotion and 5 to a downer sow. The studies included 511 pregnant sows (N=397 in Brazil and N=114 in Italy) with at least 3 locomotion evaluations in the final third of gestation to determine prevalence of lameness. A cohort sample of 30 (Farm 1) and 39 (Farm 2) sows were selected and grouped by the severity of lameness, and their productive performance, physiology, and the developmental outcomes in their offspring were assessed. Sows were grouped as not lame (G1; N = 15 Farm 1; N = 14 Farm 2), moderately lame (G2; N = 16 Farm 2), and severely lame (G3; N = 15 Farm 1; N = 9 Farm 2). In Brazil sows were grouped only as severely lame or not lame. Productivity data including gestation length, birth weight, total live/stillborn piglets, and piglets dying during the first week post-partum were collected from the selected sows. Glucocorticoid measures were performed on saliva, hair, and placenta of sows from Farm 2. A cohort sample of weaned piglets was selected from Farm 1 (N=90, 3 piglets per sow) and all piglets in the litters from Farm 2 were included. Behavioral data were collected from weaned piglets from Farm 1, skin lesions were counted to assess post-mixing aggression and exploratory behavior was measured using a combination of open field and novel object tests. Nociception threshold assessments were performed in piglets at birth, before and after castration of male piglets from Farm 2, and in weaned piglets from Farm 1. Hair was collected from newborn piglets from Farm 2 to measure cortisol. Salivary cortisol was measured in weaned piglets from Farm 1 before and after transport. After determining the data distributions, parametric and non-parametric statistical tests were used, considering significance when p < 0.05 and a tendency when p = 0.05 0.1. Results from the initial dataset indicated that lameness in pregnant sows reduced piglet weight at weaning and increased agonistic behavior in the offspring. In both the Brazilian and Italian studies, lameness reduced gestation length, whereby the gestation length in G1 sows was longer than G2 sows (Farm 2) and G3 sows (Farm 1). At birth, G1 piglets were heavier than G2 piglets (Farm 2) and G3 piglets (Farm 1). On Farm 2, nociception threshold values at birth and before castration were higher in G3 piglets than G2, and after castration were higher in G1 than G2 piglets. On Farm 1, nociception threshold after weaning was higher in G3 than G1 piglets. On Farm 1, there were fewer skin lesions after mixing in G1 than G3 piglets. On Farm 2, hair cortisol concentrations in G2 sows were higher than G3 sows and tended to be higher in male offspring from G3 than G1 sows. Placental tissue from G1 sows was more efficient in metabolizing cortisol to cortisone that from G2 sows. Finally, in Farm 1, salivary cortisol response to transport was higher in weaned piglets from G3 sows compared with piglets from G1 sows. Here we demonstrated that lameness in sows during the last third of pregnancy altered their physiology and performance and modified the phenotype of their offspring by reducing weight at birth, decreasing response to noxious stimuli, and altering behavioral and physiological responses when piglets were faced with common challenges present in the commercial farming environment.